Impact of Modeling Simplifications on Lightning Strike Simulation for Aeroengine. (10th October 2019) - Qian, Yi-fan; Ye, Zhi-feng; Zhang, Hai-bo
Abstract : With the development of electromagnetic simulation software and affordable hardware, it is allowed for us to complete simulations for EMC purposes. However, simulation demands will be immense when simulations for models with complex structures, especially aircraft components, have to be solved. Hence, it is meaningful to investigate how to minimize the computational demands. One of the solutions to reduce the simulation expense is the simplification for the simulated model. But the simplified model should be guaranteed to provide credible simulation results which do not deviate from the original model apparently. Generally, the difference between the simulation results and experimental data is estimated, or if the experimental conditions are not achieved, the comparison between the simplified model and the original one has to be analyzed, at least. This paper explores the electromagnetic simulation of a turbofan engine encountering lightning strike. With the simplifications of different components on the turbofan engine, the influences on induced currents of engine controller cables are simulated and analyzed based on the transmission-line matrix method. A combining method of components removal and geometric structure simplification is proposed to simplify the whole engine model. Simplified components include compressor, combustion chamber, turbine, and nozzle. The effects of different simplification methods are quantified, and the rationality of the simplified model is verified by simulation analysis.